Earth2014: 1 arc-min shape, topography, bedrock and ice-sheetmodels – Available as gridded data and degree-10,800 sphericalharmonics - Hirt, Christian; Rexer, Moritz (ITC, 2015)
Since the release of the ETOPO1 global Earth topography model through the US NOAA in 2009, new or significantly improved topographic data sets have become available over Antarctica, Greenland and parts of the oceans. Here, we present a suite of new 1(arc-min) models of Earth’s topography, bedrock and ice-sheets constructed as a composite from up-to-date topography models: Earth2014. Our model suite relies on SRTM30 PLUS v9 bathymetry for the base layer, merged with SRTM v4.1 topography over the continents, Bedmap2 over Antarctica and the new Greenland bedrock topography (GBT v3). As such, Earth2014 provides substantially improved information of bedrock and topography over Earth’s major ice sheets, and more recent bathymetric depth data over the oceans, all merged into readily usable global grids. To satisfy multiple applications of global elevation data, Earth2014 provides different representations of Earth’s relief. These are grids of (1) the physical surface, (2) bedrock (Earth’s relief without water and ice masses), (3) bedrock and ice (Earth without water masses), (4) ice sheet thicknesses, (5) rock-equivalent topography (ice and water masses condensed to layers of rock) as mass representation. These models have been transformed into ultra-high degree spherical harmonics, yielding degree 10,800 series expansions of the Earth2014 grids as input for spectral modelling techniques. As further variants, planetary shape models were constructed, providing distances between relief points and the geocenter. The paper describes the input data sets, the development procedures applied, the resulting gridded and spectral representations of Earth2014, external validation results and possible applications. The Earth2014 model suite is freely available via http://ddfe.curtin.edu.au/models/Earth2014/.